Contemporary issues in finance current challenges from across Europe - Bezzina, Frank; Roma<U+0304>nova, Inna.; Rupeika-Apoga, Ramona; Grima, Simon (Bingley, U.K. : Emerald, 2016)
Including studies on different topical issues in finance by the participants of the 8th international scientific conference "New Challenges of Economic and Business Development - 2016" this new work contains research from various European countries, specifically Germany, Italy, Latvia, Malta, and Poland. Chapters explore the impact of financial literacy on domestic economic activity in the Baltic States, the rapid rise of FinTech, which has changed the banking landscape, requiring more innovative solutions; Crowdfunding in the European Union, specifically examining the performance, development and perspectives; the case of Latvia to highlight the Profiles of SMEs as Borrowers, the factors that interfere with the availability of funding to the small and medium-sized companies, an analysis of Risk Parity Approach for Sovereign Fixed-Income Portfolios in Eurozone countries by looking at studies of preventive arrangements with creditors in Italy; and Mergers and Acquisitions by studying examples of best practices in Cross-Border acquisitions.
Impact of financial literacy on domesic economic activity in the Baltic states / Margarita Dunska, Kaspars Kravinskis -- Banking and Fintech: a challenge or opportunity? / Inna Romanova, Marina Kudinska -- Analysis of crowdfunding in European Union: performance perspectives / Alina Dibrova -- Misuse of derivatives: considerations for internal control / Simon Grima, Frank H. Bezzina, Inna Romanova -- Profiles of SMES as borrowers: case of Latvia / Ramona Rupeika-Apoga, Irina Solovjova -- Avoiding bankruptcy in Italy: the preventive arrangement with creditors / Alessandro Danovi, Patrizia Riva, Marina Azzola -- Mergers and acquisitions: examples of best practice in Europe and Latvia / Svetlana Saksonova, Irena Kantane -- Critical factors of pre-acquisition due diligence in cross-border acquisitions / Alen Sacek -- The FDI inflow to special economic zones in Poland / Tomasz Dorozynski, Janusz Swierkocki, Wojciech Urbaniak -- An analysis of audit report lags in Maltese companies / Peter J Baldacchino, Loraine Grech, Konrad Farrugia, Norbert Tabone.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- Banks & Banking; Finance; Banking; Finance -- Europe